HoBi‐Like Pestivirus and Its Impact on Cattle Productivity. Issue 5 (8th July 2016) - Decaro, N.; Lucente, M. S.; Losurdo, M.; Larocca, V.; Elia, G.; Occhiogrosso, L.; Marino, P. A.; Cirone, F.; Buonavoglia, C.
Summary: The clinical features and economic impact of the infection caused by an emerging group of pestiviruses, namely HoBi‐like pestivirus, in a cattle herd of southern Italy are reported. In 2011, the virus was first associated with respiratory disease, causing an abortion storm after 1 year and apparently disappearing for the following 3 years after persistently infected calves were slaughtered. However, in 2014, reproductive failures and acute gastroenteritis were observed in the same herd, leading to a marked decrease of productivity. A HoBi‐like strain closely related to that responsible for previous outbreaks was detected in several animals. Application of an intensive eradication programme, based on the detection and slaughtering of HoBi‐like pestivirus persistently infected animals, resulted in a marked improvement of the productive performances.